Catalytic processing of non-condensable pyrolysis gas from plastics: Effects of calcium supports on nickel-catalyzed decomposition of hydrocarbons and HCl sorption. (2nd November 2018) - Veksha, Andrei; Giannis, Apostolos; Oh, Wen-Da; Lisak, Grzegorz
Highlights: Catalytic upgrading of non-condensable pyrolysis gas from plastics was studied. CaCO3, Ca(OH)2, CaO and their mixtures were used as supports for Ni. All catalytic sorbents can remove HCl from non-condensable pyrolysis gas. Ca support influences on hydrocarbon decomposition and carbon formation. Catalytic activity was related to porous properties of catalytic sorbents. Abstract: Non-condensable pyrolysis gas is a suitable source of hydrocarbons for energy applications. The purpose of this study was to develop a catalytic process for selective decomposition of unsaturated hydrocarbons in the pyrolysis gas as these species compromise the operation of gas engines, gas turbines and fuel cells. The effect of different calcium supports, namely CaCO3, Ca(OH)2, CaO and their mixtures, on the performance of Ni-based catalytic sorbents during the decomposition of hydrocarbons and HCl sorption from non-condensable pyrolysis gas of mixed plastics was investigated. The plastic mixture containing low density polyethylene (40%), polypropylene (40%), polystyrene (10%) and polyvinyl chloride (10%) was initially pyrolyzed at 600 °C producing condensable oils and non-condensable gases. The non-condensable gases were further treated in a subsequent reactor at 700 °C in the presence of catalytic sorbents. All catalytic sorbents were effective for HCl sorption, decreasing the HCl concentration in the gas stream below detectable levels. However, the choice of calcium support had a substantial effect on the catalytic decomposition of hydrocarbons and the properties of produced carbon deposits. CaCO3, Ca(OH)2 and their mixture at 1:1 ratio by mass loaded with Ni showed higher catalytic activity towards the decomposition of hydrocarbons compared to CaO and a mixture containing CaO, CaCO3 and Ca(OH)2 at 1:1:1 ratio by mass. Furthermore, carbon deposits produced on the surface of Ni supported on CaCO3, Ca(OH)2 and their mixture contained multi-walled carbon nanotubes, whereas carbon deposits produced on Ni supported on CaO and the mixture containing CaO had non-filamentous morphology. The observed results can be attributed to the low BET specific surface areas and pore volumes of CaO-containing catalytic sorbents which could limit the dispersion of Ni resulting in low catalytic activity.